Differences between sexes in thermoregulatory responses and exercise time during endurance exercise in a hot environment following pre-cooling with ice slurry ingestion - Iwata, R.; Kawamura, T.; Hosokawa, Y.; Chang, L.; Suzuki, K.; Muraoka, I. (Journal of Thermal Biology, 2020)
This study aimed to examine differences between sexes in thermoregulatory responses and exercise time after ice slurry ingestion in a hot environment. Twenty-four healthy adults (male n=12, body weight (BW)=65.8±10.3; female n=12, BW=58.2±10.0) ingested 7.5g/kg of either ice slurry at -1°C (ICE) or control water at 20°C (CON) before cycling at 55%VO2 max in a hot environment (controlled at 38°C, 40% relative humidity). Rectal (Tre) and skin (Tsk) temperature, heart rate, sweat rate, respiratory gases, ratings of thermal sensation (TS), thermal comfort (TC), and rating of perceived exertion (RPE) were measured. Ice slurry did not improve exercise time in both sexes despite Tre was significantly lower in ICE than CON in both sexes. Tre, Tsk, HR, sweat rate and TS did not differ between sexes. TC and RPE in ICE were significantly higher during exercise in males than in females. In conclusion, there were no sex differences in the effects of pre-cooling with ice slurry ingestion; however, pre-cooling with ice slurry may be more effective in mitigating ratings of TC and RPE in females than males.